Development of Single LED Display 3 Colours for Brake, Signal, Reverse and Back Light Car - Muhammad Ikram, Mohd Rashid; Mohd Amirul Shafiq, Deraji; Suliana, Ab Ghani (2014)
Nowadays, most of the cars used the bulb for brake, signal, reverse and backlight for lighting. Unfortunately, the life span of the bulb is quiet short. The development of single Light Emitting Diode (LED) has been designed to cater the problem conventional brake, signal, reverse and backlight car. Using C language as a command language to program the Arduino ATmega 2560 Microcontroller as main controller to control the output/Red, Green, Blue (RGB) LED. The RGB LEDs has been used to replace the bulb light to solve the car lighting problem. The single LED display can raise the level of brightness and longer life span for brake, signal, reverse and back light lighting.